Plant-based corrosion inhibitor from extracts of Cerbera Odollam: study of inhibition efficiency on mild steel in various electrolyte conditions - Mohd Rosli, Nur Adryna (2018)
Mild steel has been greatly used for pipeline and machinery application in oil and gas industry, where exposal to corrosive environment is anticipated. Type of metals influenced by environmental properties such as existence of corrosive gas, has increased the possibility for corrosion to occur even faster. Thus, corrosion inhibitors in various types were introduced. Previously, researchers were using inorganic and synthetic corrosion inhibitors. Other than having high manufacturing cost, their high environmental toxicity threatening marine life. Hence, researchers’ attention shifted to organic inhibitor from plant extracts. However, the finding of active ingredients and its efficiency is still at scarce. In this experimental study, efficiency of oil extracts from sea mango (Cerbera Odollam) seeds was investigated in terms of its corrosion inhibition potentials via weight loss measurements and potentiodynamic Tafel polarization technique. It was found that sea mango oil reduced corrosion rate and increased inhibition efficiency as inhibitor concentration and pH test solution increased from 2 to 7. Structural characterization of active corrosion compounds in oil samples was analysed using FT-IR and GCMS. Phytochemical screening tests were performed to detect the presence of saponin, phenol, steroid and tannin. The inhibitive properties of these extracts were likely due to the presence of oxygen and nitrogen atoms, which have evidenced from FTIR and GCMS. The adsorption of sea mango oil was found to best fit Langmuir adsorption isotherm.